2004
DOI: 10.1074/jbc.m312822200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the CKI-CDK-Rb-E2F Pathway in Full Genome Hepatitis C Virus-expressing Cells

Abstract: Hepatitis C virus (HCV) causes persistent infection inhepatocytes, and this infection is, in turn, strongly associated with the development of hepatocellular carcinoma. To clarify the mechanisms underlying these effects, we established a Cre/loxP conditional expression system for the precisely self-trimmed HCV genome in human liver cells. Passage of hepatocytes expressing replicable full-length HCV (HCR6-Rz) RNA caused upregulation of anchorage-independent growth after 44 days. In contrast, hepatocytes express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 48 publications
1
58
1
1
Order By: Relevance
“…and S.M.L., unpublished data), indicating that Rb is negatively regulated by different strains of HCV that are widely divergent genetically. These findings differ significantly from those reported by TsukiyamaKohara et al (28), who described an initially positive then negative effect on Rb after expression of HCV proteins in HepG2 cells. We found that the negative regulation of Rb abundance by replicating HCV RNA is due to the NS5B RNA-dependent RNA polymerase.…”
Section: Discussioncontrasting
confidence: 99%
“…and S.M.L., unpublished data), indicating that Rb is negatively regulated by different strains of HCV that are widely divergent genetically. These findings differ significantly from those reported by TsukiyamaKohara et al (28), who described an initially positive then negative effect on Rb after expression of HCV proteins in HepG2 cells. We found that the negative regulation of Rb abundance by replicating HCV RNA is due to the NS5B RNA-dependent RNA polymerase.…”
Section: Discussioncontrasting
confidence: 99%
“…The overexpression of Mad2, while Mad1 is unaffected, will disturb the normal ratio of these components in the mitotic checkpoint complex (14). The detailed mechanism of Rb suppression by core protein remains obscure (4,13,61). Our studies showed that the core protein inhibits Rb transcription through the suppression of the Rb promoter activity and that core protein is the only HCV protein capable of inhibiting Rb transcription.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, core protein has been shown to impair cell cycle regulation in stably transformed Chinese hamster ovary cells (16). Core protein also affects the function of human Rb, LZIP (a homologue to the Drosophila melanogaster BBF2/dCREB-A protein), and other cell growth regulatory proteins, such as 14-3-3 (1,4,13,20,61). The Rb gene can uncouple cell cycle progression from mitotic control by activation of mitotic checkpoint protein Mad2, leading to genomic instability (14).…”
mentioning
confidence: 99%
“…Briefly, following 30 min of preincubation without ATP, CTP, or UTP, 100 nM HCV RdRp was incubated in 50 mM Tris-HCl (pH 8.0), 200 mM monopotassium glutamate, 3.5 mM MnCl 2 , 1 mM dithiothreitol (DTT), 0.5 mM GTP, 50 M ATP, 50 M CTP, 5 M [␣-32 P]UTP, 200 nM RNA template (SL12-1S), 100 U/ml human placental RNase inhibitor, and the lipid (amount indicated below) at 29°C for 90 min. 32 P-labeled RNA products were subjected to 6% polyacrylamide gel electrophoresis (PAGE) containing 8 M urea. The resulting autoradiograph was analyzed with a Typhoon Trio plus image analyzer (GE).…”
Section: Methodsmentioning
confidence: 99%